PENILAIAN KINERJA PORTOFOLIO SAHAM DARI VARIABEL MAKRO EKONOMI (Studi Saham – Saham Manufaktur dan Perbankan di BEI Tahun 2005-2009) - Utami, Yuni; Faqihudin, M (PERMANA, 2012)
Portfolio in capital market context resembles financial assets of combination of several shares invested by investor in order to obtain optimal return with a minimum risk. The selected shares are shares with ultimate performance or out perform. The aim of study is to acquire empirical from the performace of each share that can be positively predicted by makro economic variables, and to measure how big is the influence of each variable. Population in this study are manufacture and banking  sharres listed at BEI during 2005 ? 2009 for as much as 158 company. Sample for this study are 136 selected company from population. Research data is obtained at BEI, BI and BPS . The entire model in this research is analyzed using logistic regression. The technique shows  that  the four variables  that can predict an out perform  share is unemployment, Product Domestic Bruto (PDB), inflation, and Kurs variables. It has profitability level of 0,000; 0.000;0,000; and 0,055 significance level  at ? 10%. However, the remain one variable is SBI rate can not Predicted performance share  respectively are not significant at ? 10%, thus can not predict and out perform share. From classification matrix with 50% cut off this model can result overall classification  value of  63,1%, which shows that the model is acceptable. Keyword : performance share, portfolio, makro economic variables